Lincoln, Neb., Rev. Ordinances pt. 2, ch. 14, art. 26, § 5 (1895) - (:unkn) unknown (My University, 1895)
It shall be unlawful for any parent, guardian, or other person having the care and custody of any minor, to purchase for or give to any such minor or knowingly to permit any such minor to have any toy pistol, toy gun, or other toy arm or arms, or sling shot, out of which any leaden or other dangerous missiles may be discharged.§
Keywords: TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES